2016
DOI: 10.1002/ajpa.22952
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional consequences of folivory in a small‐bodied lemur (Lepilemur leucopus): Effects of season and reproduction on nutrient balancing

Abstract: We conclude that these animals prioritize protein over non-protein energy intake as dietary protein is in limited supply, and that thermoregulation poses higher energetic costs than reproduction in this species. While protein intake did not differ across female reproductive states, the relative protein content of the diet was highest during the lactation period, indicating that the balance of non-protein to protein intake may be more important than absolute intake. Dry matter intake was high compared to other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
30
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 86 publications
(95 reference statements)
3
30
2
Order By: Relevance
“…The Eulemur clade are flexible frugivores [73], with high levels of folivory recorded in western populations during the dry season [79]. Propithecus and Lepilemur are both considered folivorous [71,[80][81][82], consuming leaves throughout the year [73,80,83] and fruit when available during the rainy season [43,73,80,84]. We found that the predicted functional composition of lemur microbiomes reflected differences in carbohydrate Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Eulemur clade are flexible frugivores [73], with high levels of folivory recorded in western populations during the dry season [79]. Propithecus and Lepilemur are both considered folivorous [71,[80][81][82], consuming leaves throughout the year [73,80,83] and fruit when available during the rainy season [43,73,80,84]. We found that the predicted functional composition of lemur microbiomes reflected differences in carbohydrate Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although sifaka and sportive lemurs are both hindgut fermenters, their digestive strategies lie at opposite ends of the continuum observed for primates. Sifaka employ an "efficiency" strategy, characterized by low intake, long mean retention time, and high fiber digestibility [91], while sportive lemurs use an "intake" strategy, with high intake, short mean retention time, and low fiber digestibility [68,83].…”
Section: Discussionmentioning
confidence: 99%
“…The total amount of potentially fermentable plant food items (gum, leaves, flowers) is still lower in proportion than what was observed for the largest N. bengalensis, which theoretically should have the largest fermentation capacity of the slow lorises due to its large size (Das et al, 2014). With an average weight of 900 g, N. javanicus may have similar fermentation capabilities as the 1 kg white-footed sportive lemur (Lepilemur leucopus), which is entirely folivorous, as both genera exhibit complex large intestines with a welldeveloped cecum (Droscher et al, 2016). However differences in gut microflora, surface area and presence of diverticula will impact fiber digestibility.…”
Section: Characterizing the Diet Of The Javan Slow Lorisesmentioning
confidence: 86%
“…; both of which contained FIG URE 2 Scatter plot of the relationship between availability and percentage contribution of foods part of the Javan slow loris (Nycticebus javanicus) diets on a fresh weight basis. With an average weight of 900 g, N. javanicus may have similar fermentation capabilities as the 1 kg white-footed sportive lemur (Lepilemur leucopus), which is entirely folivorous, as both genera exhibit complex large intestines with a welldeveloped cecum (Droscher et al, 2016). Dry season was from October until April and wet season from mid April until October (see "Methods").…”
Section: Characterizing the Diet Of The Javan Slow Lorisesmentioning
confidence: 99%
See 1 more Smart Citation